Pruebas de laboratorio elementales de apoyo en el diagnostico precoz de leptospirosis machala 2018-2019 . - Castillo Macas, Viviana Mariuxi (Machala : Universidad Técnica de Machala, 2019)
INTRODUCTION: The leptospirosis according to the World Organization of Health WHO in 2008 refers that it is a global health problem in the humid tropical and subtropical areas where the majority of developing countries are and with greater significance in those that have a temperate climate , due to the difficult timely diagnosis in primary health care since it frequently produces a mild disease or with nonspecific symptoms such as fever, myalgia, retro ocular pain, it usually results in a sub-registration of cases, leading to treatment late and ineffective. GENERAL OBJECTIVE: To establish the differences between laboratory tests for the early diagnosis of leptospirosis by reviewing scientific articles for an adequate treatment of the patient in primary health care. METHODS: this investigative work is carried out through the use of academic data search platforms and / or journals: ScienceDirect, Cochrane, Pubmed, Medline, Google Scholar of periods from 2013 to 2018. DEVELOPMENT: the selection of articles that comply with the parameters mentioned above and that have international guarantees and are within the research levels between quartiles Q1 and Q2; a comparison was made between the clinical characteristics between leptospirosis, dengue and urinary tract infection. CONCLUSIONS: Leptospirosis is one of the main zoonoses of impact in our region, this added to its presentation of febrile majority and clinical similarity with pathologies such as dengue without warning signs and UTI, lead to an underreporting of cases in the centers of primary care, here is the importance of using and interpreting laboratory tests such as complete blood count, NS1 glycoprotein, an elementary urine test to make an early diagnosis, give proper treatment and avoid complications.
INTRODUCCIÓN: La leptospirosis según la organizacion mundial de la salud OMS en el 2008 refiere que es un problema de salud mundial en las áreas tropicales y subtropicales, debido al difícil diagnóstico oportuno en la atencion primaria de salud y a que frecuentemente produce una enfermedad leve o con síntomas inespecíficos por lo general resulta en un sub-registro de los casos,conllevando asi a un tratamiento tardio e ineficaz. OBJETIVO GENERAL: Establecer las diferencias entre los exámenes de laboratio para el diagnóstico precoz de leptospirosis mediante la revisión de artículos científicos para un tratamiento adecuado del paciente en la atencion primaria de salud. MÉTODOS: se realiza este trabajo investigativo mediante la utilización de plataformas de búsqueda de datos académicos y/o revistas: Cochrane, Pubmed, Medline, Google Académico de periodos de comprendidos desde el año 2013 hasta 2018. DESARROLLO: Se realiza la selección de artículos que cumplan con los parámetros mencionados anteriormente y que cuenten con avales intenacionales, se realizó una comparación entre las características clínicas entre leptospirosis,dengue e infección de vías urinarias. CONCLUSIONES: La Leptospirosis es una de las principales zoonosis en nuestra región, debido a su presentación de mayoría febril y semejanza clínica con patologías tales como dengue sin signos de alarma e IVU, conllevan a un subregistro de los casos en los centros de atención primaria, he aqui la importancia utilizar e interpreter los examenes de laboratorio tales como el hemograma complete,la glicoproteína NS1,un examen elemental de orina para asi realizar un diagnostico precoz, dar un tratamiento adecuado.
Keywords: LEPTOSPIROSIS; FIEBRE; DENGUE; IVU